La justicia en un Estado plurinacional con garantismo penal: interculturalidad en ciernes (Tema Central) - Narváez Collaguazo, Roberto Esteban (2020)
Since 2008, Ecuador introduced in its Constitution the principles of plurinationality and interculturality, as a way to recognize the cultural diversity present in the country. It is precisely this cultural diversity that maintains certain cultural practices framed in the traditions and linked to different forms of life, that still do not achieve an understanding from the public institutions and generate conflicts in the judicial field. The article develops a juridical and anthropological analysis, around a case study, about traditional ritual hunting activities, typifying a penal type, where the limitation of the principle of interculturality and the judicial processing that is done to indigenous population is discussed. In this way, the article seeks to show need for the implementation of the constitutional principles of plurinationality and interculturality in a space for equitable dialogue, where these limitations in the approach to cultural diversity could be assumed, but, above all, recognizing the need for an efficient weighting during the exercise of criminal law under the principle of ultima ratio.